KELUARGA SEBAGAI LEMBAGA PERTAMA PENDIDIKAN ISLAM - Fitri, Agus Zainul (Jurnal Pendidikan Islam, 2016)
Family is the first educational institution for the children where the parents are becoming the first educator. The parents are in a nature fully responsible for their children, should educate their children toward optimal growth and development of nature. Errors in their children's education would be fatal. The child may deviate from firsthand the potential of human kindness has turned into a low quality. Thus an important role, duties and responsibilities of parents, it is then to be understood thatheformal educational institutions and non-formal, organized by the government and society, and teachers or other education personnel is a successor of the parental role in fostering and developing their children. There are three parenting parents towards their children, parenting there are democratic, authoritarian, and permissive. The three parenting is regarded as a good way to educate is a democratic parenting style, but still maintaining the principles of universal and absolute values associated with religion, especially Islam.that is plurality.similiarity of right and egaliter Authoritarian patterns worth doing if it relates to the issue of faith and conviction and worship as well as things that are considered harmful to The child. While permissive pattern can also be applied to children aged adults.